Failure of Preactivated Human Blood Platelets to Restore Defective Thromboxane Synthesis despite Prolonged Incubation in Plasma - Stockschläder, Marcus; Scharf, Rüdiger E (Thrombosis and Haemostasis, 1989)
Acquired platelet storage pool disease has been shown to be associated with reduced platelet thromboxane synthesis. However, the mechanisms for this dysfunction are incompletely understood. The present experiments were designed to evaluate some of the possible defects which may account for impaired thromboxane formation in human platelets previously exposed to thrombin in vitro. Washed platelets pretreated with 0.5 U/ml thrombin for 20 sec and subsequently recovered as single degranulated platelets were incapable of forming normal amounts of thromboxane upon a second stimulation with thrombin (as compared to Tyrode-pretreated control platelets). In contrast, thrombin-degranulated platelets released additional amounts of thromboxane in response to arachidonate, or collagen, indicating that short-time exposure to thrombin does not irreversibly inactivate platelet cyclooxygenase or thromboxane synthetase. Upon incubation of the thrombin-pretreated platelets in autologous plasma in the presence of 14C-arachidonate, the label became associated with the platelets to the same extent as with control platelets. However, the platelets did not recover their ability to synthesize normal amounts of thromboxane upon restimulation with thrombin, and only about half of the label was lost from the thrombin-pretreated platelets as compared to control platelets in response to thrombin. The ability of collagen to cause loss of 14C-arachidonate and formation of thromboxane was the same regardless of whether or not the platelets had been pretreated with thrombin. Incubation of platelets in plasma in the presence of added arachidonate for 90 min resulted in complete refractoriness to a second stimulation with thrombin but not with collagen. However, the control platelets also lost most of their ability to synthesize thromboxane when incubated with arachidonate for 90 min and thereafter stimulated with thrombin. Thus, the presence of added arachidonate affects the thrombin-inducible thromboxane synthesis after prolonged incubation of human platelets in plasma. Our observations suggest that depletion of endogenous arachidonate is not a major cause for the defective thrombin-induced thromboxane synthesis in thrombin-pretreated platelets. It is more likely that impaired mobilization of endogenous arachidonic acid explains this dysfunction. Defective mobilization of arachidonate in thrombin-degranulated platelets may be due to agonists-specific receptor desensitization, but the responsible mechanism has not been identified.
Keywords: Degranulated platelets; Thrombin; Collagen; Thromboxane synthesis; Arachidonic acid metabolism; Receptor desensitization